Hepatic resection for hepatocellular carcinoma in cirrhotic patients with portal hypertension. Issue 4 (November 2016) - Zakaria, Hazem M.; Gad, Emad H.; Nada, Ali; Abdelaleem, Anwar A.; Maher, Doha; Abdel Samea, Mohammad E.; Sabry, Alyaa
Abstract : Aim: Hepatic resection (HR) in cirrhotic patients with hepatocellular carcinoma (HCC) and portal hypertension (PHT) is not recommended, according to international guidelines. The aim of the present study was to determine the outcome of HR for HCC in cirrhotic patients with PHT. Methods: The present study was a single institutional, retrospective study of 170 Child–Pugh class A cirrhotic patients who underwent HR for HCC from 2011 to July 2015. The patients were divided into two groups, according to the presence and absence of PHT. Results: PHT was present in 91 patients (53.5 per cent). The postoperative morbidity was insignificantly higher in patients with PHT than patients without PHT (31.9 per cent vs 25.3 per cent, respectively, P = 0.36). Patients with PHT showed 90‐day perioperative mortality (3.3 per cent), which was similar to patients without PHT (2.5 per cent). In the subgroup analysis, the 1‐, 3‐ and 5‐year overall survival for patients with limited HR was 90.3 per cent, 74.3 per cent and 66.2 per cent, respectively, for patients with PHT, and 93.9 per cent, 80.9 per cent and 73.6 per cent, respectively, for patients without PHT, without a significant statistical difference ( P = 0.38). Conclusion: HR in Child–Pugh class A cirrhotic patients with PHT is a safe and effective procedure with good short‐ and long‐term outcomes in comparison to patients without PHT, especially those with limited liver resection.